2022
DOI: 10.3390/cells11091548
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship between Obesity and Pre-Eclampsia: Incidental Risks and Identification of Potential Biomarkers for Pre-Eclampsia

Abstract: Obesity has been steadily increasing over the past decade in the US and worldwide. Since 1975, the prevalence of obesity has increased by 2% per decade, unabated despite new and more stringent guidelines set by WHO, CDC, and other public health organizations. Likewise, maternal obesity has also increased worldwide over the past several years. In the United States, pre-pregnancy rates have increased proportionally across all racial groups. Obesity during pregnancy has been directly linked to obstetric complicat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
20
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(22 citation statements)
references
References 65 publications
1
20
0
1
Order By: Relevance
“…The global increase in the prevalence of obesity in women [ 7 , 8 ] requires a better understanding of the sex-specific drivers and function of fat depots in relation to sex hormone status including menopause and post-menopause. In addition, further investigations are required to obtain a complete picture of the functions of the maternal fat depots, as the incidence of gestational diabetes mellitus and pre-eclampsia, disorders of pregnancy with short- and long-term consequences for mother and child, continues to increase due to maternal obesity [ 120 , 121 ]. A better understanding of the mechanisms and molecular players of sexual dimorphism will permit us to consider therapies to limit the risk of metabolic and cardiovascular pathologies in the context of central obesity and aging.…”
Section: Discussionmentioning
confidence: 99%
“…The global increase in the prevalence of obesity in women [ 7 , 8 ] requires a better understanding of the sex-specific drivers and function of fat depots in relation to sex hormone status including menopause and post-menopause. In addition, further investigations are required to obtain a complete picture of the functions of the maternal fat depots, as the incidence of gestational diabetes mellitus and pre-eclampsia, disorders of pregnancy with short- and long-term consequences for mother and child, continues to increase due to maternal obesity [ 120 , 121 ]. A better understanding of the mechanisms and molecular players of sexual dimorphism will permit us to consider therapies to limit the risk of metabolic and cardiovascular pathologies in the context of central obesity and aging.…”
Section: Discussionmentioning
confidence: 99%
“…Ця асоціація не залежала від соціально-економічно-го статусу жінок, оскільки спостерігалася як у заможних, так і в малозабезпечених спільнотах [35]. Шведське дослідження, яке фактично передувало дослідженню в Танзанії, підтвердило важливість ожиріння як фактора ризику, оскільки підвищений ІМТ збільшував ризик для всіх типів прееклампсії та її ускладнень, включаючи передчасні пологи [6]. Подібну підтримку надає проспективне дослідження, проведене в Бразилії в 2013 році.…”
Section: результати та їх обговоренняunclassified
“…Beneventi et al, 2020 investigated maternal and fetal plasma levels of leptin in pregnancies complicated by obesity and preeclampsia. The authors found that pregnant women with obesity had higher serum leptin levels than normal-weight subjects with and without hypertension or normotensive subjects with obesity (Larsen et al, 2019;Beneventi et al, 2020;Abraham and Romani, 2022).…”
Section: Introductionmentioning
confidence: 99%